2011
DOI: 10.1108/17511871111172321
|View full text |Cite
|
Sign up to set email alerts
|

Leadership development initiatives underlie individual and system performance in a US public healthcare delivery system

Abstract: Purpose -The purpose of this case study was to gather participants' perceptions of the impact of Memorial Healthcare System's Pillars of Leadership Academy's leadership development programs on an individual, professional and organizational level. Design/methodology/approach -Through a mixture of in-person and telephone structured interviews, the researchers collected and analyzed qualitative data to explore the experiences of participants from the leadership development programs. Findings -The major themes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
0
24
0
7
Order By: Relevance
“…), and the USA (Borkowski et al . ) identifying the need for purposeful education for leadership in nursing. The content of educational programmes must be informed by an understanding of the skills and capabilities required of nurse leaders to ensure that educational initiatives foster and support the acquisition of these skills (Dignam et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and the USA (Borkowski et al . ) identifying the need for purposeful education for leadership in nursing. The content of educational programmes must be informed by an understanding of the skills and capabilities required of nurse leaders to ensure that educational initiatives foster and support the acquisition of these skills (Dignam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Effective leadership is regarded as essential in contemporary health systems as evidenced by research in Australia (Garling 2007, Bennet 2009), New Zealand (Marinelli-Poole et al 2011), Scotland (Edmonstone 2011), Sweden (Grill et al 2011), and the USA (Borkowski et al 2011) identifying the need for purposeful education for leadership in nursing. The content of educational programmes must be informed by an understanding of the skills and capabilities required of nurse leaders to ensure that educational initiatives foster and support the acquisition of these skills (Dignam et al 2012: 69).…”
Section: Discussionmentioning
confidence: 99%
“…To be able to guide and direct effectively, the head librarian must demonstrate good leadership. This is because leadership entails the ability to communicate the value, vision and mission of the organization in order to motivate employees (Borkowski, Decker, Weber, Padro and Loungo (2011) [12]. One function of the head librarian above all is to use his leadership style to persuade and coordinate all activities of subordinates to willingly contribute to organizational goals in accordance with their maximum capabilities.…”
Section: Leadershipmentioning
confidence: 99%
“…Limsila and Ogunlana (2007) indicated that an appropriate leadership style leads to employee satisfaction and it is a good indicator to prove that a better style might lead employee to work effectively (Likhitwonnawut, 1996). Here, leaders should be able to communicate the values, vision and mission of their organization in order to motivate the employees (Borkowski et. al., 2011).…”
Section: Introductionmentioning
confidence: 99%